Exploring the association between optimism and quality of life among informal caregivers of persons with dementia. (18th July 2018) - Ruisoto, Pablo; Contador, Israel; Fernández-Calvo, Bernardino; Palenzuela, David; Ramos, Francisco
ABSTRACT: Objective: We aimed to analyze the relationship between optimism and quality of life (QoL) among informal caregivers of patients with dementia (PWD). Design: In this cross-sectional study, a hierarchical multiple linear regression analysis was used to determine the association between optimism and caregiver's QoL after controlling the effect of different covariates, including burden. Participants: A sample of 130 PWD and their informal caregivers underwent a comprehensive protocol of assessment. Measurements: Caregivers completed the Battery of Generalized Expectancies of Control Scales, the Zarit Burden Interview, and the World Health Organization Quality of Life-Brief as measure of QoL. Optimism was estimated based on the combination of three expectancies of control, namely, self-efficacy, contingency, and success. Results: QoL correlated positively with optimism and negatively with burden. Optimism predicted each dimension of QoL, even after controlling for the effect of sociodemographic, care-recipients' clinical covariates, and burden in all models. Conclusion: Optimism consistently predicted well-being and QoL in informal caregivers of PWD.